Latest advances in FNTD technology and instrumentation. (April 2020) - Akselrod, Mark; Fomenko, Vasiliy; Harrison, Jonathan
Abstract: The next technological breakthrough in tools for radiation protection, medical dosimetry and radiobiology research was achieved with Fluorescent Nuclear Track detectors (FNTD) that have some important advantages in measuring neutrons, high energy heavy charge particles (HCP) and even electrons and photons. Second generation of FNTD reader with improved image quality and 30 times faster scanning was developed. Highlights: Fluorescent Nuclear Track detectors (FNTD) are for measuring neutrons, heavy charge particles (HCP) and even electrons and photons. Second generation of FNTD reader with improved image quality and 30 times faster scanning was developed. Convolution Neural Network algorithm was applied to image processing of fluorescent tracks.